Adaptation of Captivity - Ilijić, Ljeposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Adaptation or customisation is the way in which man kept alive in changing circumstances. In the case of prisoners, it is identified as the process of accepting the norms and rules of the prison system that is formal. How does the flow of the process and the factors that determine this proces and what is its impact on the ultimate success of prison sentences, are just some of the questions they’re looking for theorists from the field of penology. In this paper, attention has been devoted to the search for answers to these questions, as well as the analysis of the results of previous research on this issue.